Re-architecting the firm for increased value: How business models are adapting to the new AI environment - Gozde Turktarhan; David Aleong; Chandra Aleong (Journal of Global Business Insights, 2022)
This paper is an examination of how technology, specifically artificial intelligence (AI), brings about changes in business models, with corresponding impacts on the fields of economics and business. Concepts such as value creation and competitive advantage have cascading effects on organizational culture and the functional framework of a firm. Data creation, management, and curation using media platforms enable enhanced scalability and logistics management such that the firm can be re-architected around a digital core. Organizational structure with functions such as marketing and human resource management are integral links in the automated value network anticipating and responding to customers’ needs while providing increasing marginal rates of return to the firm. The thematic analysis used as a methodological research tool yielded examples of companies that have embraced AI platforms and this paper describes the tremendous growth these companies are experiencing. This paper critically assessed and highlighted the enormous benefits of the new business entity due to AI. There are limitations to algorithms based on historical data such as the perpetuation of bias, loss of privacy, and anti-competitive practices. The implications described include how to harness the potential benefits of technology while mitigating the drawbacks, such as the rise in the anti-competitive dominance of oligopolistic players.